The effect of passive measures on thermal comfort and energy conservation. A case study of the hot summer and cold winter climate in the Yangtze River region. (January 2018) - Yao, Runming; Costanzo, Vincenzo; Li, Xinyi; Zhang, Qiulei; Li, Baizhan
Abstract: The energy consumption for heating and cooling of buildings in the cities located within the boundaries of the Hot Summer and Cold Winter (HSCW) zone in China is rapidly increasing due to the increased comfort expectations from well-resourced occupants. Guidance on how and to what extent it is possible to improve energy efficiency of buildings is thus required by policy makers as well as designers and building managers. The aim of this study is to demonstrate how the use of climate-sensitive passive design solutions can help the improvement of indoor thermal conditions while reducing the energy needs and ultimately carbon emissions. An extensive parametric analysis of several passive strategies such as building orientation, thermal insulation, glazing area, shading devices, air tightness and natural ventilation, is carried out for a typical apartment block located in the cities of Chongqing, Changsha and Shanghai, which lay respectively in the upper, middle and downstream of the Yangtze River. Detailed hourly dynamic simulations show how it is possible to extend the non-heating/cooling period and reduce the peak loads, highlighting the potentialities of each strategy according to different climate constraints. The recommended strategies provides quantitative guidance to either design of new or retrofitting of existing buildings. This research contributes to the building energy conservation knowledge for policy-makers, developers and building designers with insight on the feasibilities of the application of passive measures for residential buildings located in the Yangtze River region with hot summer and cold winter climates. Highlights: Passive measures for the residential buildings in the Yangtze River Valley are studied; An index called PEPS (Potential Effectiveness of Passive Solutions) is introduced to assess the effectiveness; The PEPSs are 18%, 20% and 24% for Changsha, Chongqing and Shanghai respectively; Passive measures can significantly extend non heating/cooling demand period and the peak load demand; An integrated solution of passive, active and operational behavioural is the key strategy.